2016
DOI: 10.1007/s10096-016-2647-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on Staphylococcus aureus carriage in psoriasis, acne and rosacea

Abstract: Staphylococcus aureus might amplify symptoms in chronic inflammatory skin diseases. This study evaluates skin and mucosal colonization with S. aureus in patients with psoriasis, acne and rosacea. A systematic literature search was conducted. Both odds ratios (OR) for colonization in patients versus controls and the prevalence of colonization in patients are reported. Fifteen articles about psoriasis and 13 about acne (12 having a control group) were included. No study in rosacea met our inclusion criteria. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 66 publications
0
35
0
5
Order By: Relevance
“…Although more than 30% of healthy individuals are colonized asymptomatically by S. aureus 75,76 , it can cause a wide spectrum of infections: some are limited to a single hair follicle (furuncle), others involve subcutaneous tissues (cellulitis), and the most serious feature potentially fatal penetration into any organ in the body, including bone (osteomyelitis), bloodstream (bacterial sepsis), and heart valves (bacterial endocarditis). S. aureus has also been implicated in the pathogenesis of chronic diseases such as atopic dermatitis 22,7779 , and more recently in systemic lupus erythematosus with renal and skin involvement 80 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
“…Although more than 30% of healthy individuals are colonized asymptomatically by S. aureus 75,76 , it can cause a wide spectrum of infections: some are limited to a single hair follicle (furuncle), others involve subcutaneous tissues (cellulitis), and the most serious feature potentially fatal penetration into any organ in the body, including bone (osteomyelitis), bloodstream (bacterial sepsis), and heart valves (bacterial endocarditis). S. aureus has also been implicated in the pathogenesis of chronic diseases such as atopic dermatitis 22,7779 , and more recently in systemic lupus erythematosus with renal and skin involvement 80 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
“…Few studies which investigated this subject revealed increased skin colonization with S. aureus (Tomi et al 2005; Totté et al 2016b)—in more than 50% of psoriatics (reaching 100% of those with erythroderma) vs. 12% of healthy controls. Moreover, disease activity was significantly correlated with toxogenic strains (Balci et al 2009; Tomi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Increased colonization of S . aureus in psoriatic skin has been reported previously in several small studies, but only a few of these examined unaffected skin from psoriasis patients [ 44 ]. Our data revealed a significant increase of colonization in both psoriatic lesional and non-lesional sites compared to the baseline levels of S .…”
Section: Discussionmentioning
confidence: 99%